Offshoring of Construction Engineering Services-top strategy, work processes and challenges -a two-way case study perspective between Sweden and India respectively Romania - NASTEFSKI, OLIVER LÖFMAN (My University, 2019)
Currently planning and executing the largest urban city development project in the Nordic region, the city of Gothenburg (Sweden) is forecasting an urgent need of professionals within all chains of construction projects if the projects are to be realized. This urgent need can furthermore be expanded to other cities in Sweden such as Stockholm. The demand can only be met if several strategies are incorporated, one of which is to utilize competence and resources from other countries, hence, adhering to using offshoring as a strategy for construction engineering services. The purpose of this master thesis is therefore to analyze how a large global company within the sector works with implementing strategies connected to offshoring. Furthermore an aim is to analyze how the design process is conducted in the global virtual teams being present and to investigate which challenges which are the most prominent. A qualitative research approach together with a case study have been used in this thesis. The theoretical framework have encompassed three broad areas in total, namely strategy, work processes and challenges in global virtual teams. This was done in order to get a holistic picture of the whole chain when using offshoring as a strategy. Cost reductions and resource seeking was stressed as the fundamental strategic motives by the theoretical framework, whereas the challenges were mostly connected to communication, culture and partly interpersonal aspects. The case study has been conducted with a two-way perspective by interviewing both managers and engineers in Sweden, India and Romania, where the two later are used as offshoring destinations. The empirical findings suggests that offshoring challenges might not be as much related to language barriers and cultural aspects as suggested by previous research. The findings rather highlight the fact that the lack of project management skills from the Swedish engineers is a large contributor to obstacles in projects. In terms of strategic reasons for adapting an offshoring element, the findings correspond to much of the recent studies adhering to the ever increasing importance of seeking resources, i.e. not only searching for cost reductions. Considering that the company in hand is relatively new with offshoring services to India and Romania, a rigorous apparatus including clear strategic moves and adapted work processes has already been put into place. Furthermore a healthy awareness regarding challenges connected to the work is present among both engineers and managers in respective country. An improvement of project management skills among the Swedish engineers, coaching of senior employees which struggle with working in global virtual teams, and an encouragement of team building could benefit the organization.
Keywords: Samhällsbyggnadsteknik; Civil Engineering